SAE Technical Paper Series 2011
DOI: 10.4271/2011-01-1772
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Comparison of Residual Gas Enhanced HCCI using Trapping (NVO HCCI) or Rebreathing of Residual Gases

Abstract: A comparison between throttled and unthrottled spark ignition combustion with residual enhanced HCCI combustion is made. Early intake valve closing and late intake valve closing valve strategies for unthrottled spark ignition combustion are evaluated and compared. Approximately 3-6 percent relative improvement in net indicated efficiency is seen when comparing unthrottled spark ignition combustion with throttled spark ignition combustion depending on valve strategy and engine speed. The relative improvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Additional engine specifications are listed in Table II. For further details on the engine and the control and data acquisition system, see [24].…”
Section: Methodsmentioning
confidence: 99%
“…Additional engine specifications are listed in Table II. For further details on the engine and the control and data acquisition system, see [24].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have been completed on the use of internal exhaust gas retention for gasoline PPC engines. [20][21][22] These investigators compared the rebreathing valve strategy with the use of NVO (with and without fuel injection). They found lower heat losses with the rebreathing strategy, but combustion stability was weaker.…”
Section: Examples Of Previous Workmentioning
confidence: 99%
“…In the exhaust rebreathing strategy, the exhaust valve opens again while the intake valve is opened so that the exhaust gases flow back to the cylinder. Borgqvist et al 7 showed that a rebreathing HCCI engine can achieve higher thermal efficiency than a NVO HCCI engine. In addition, Babajimopoulos et al 8 reported that the exhaust rebreathing strategy leads to more homogeneous mixtures than the NVO strategy.…”
Section: Introductionmentioning
confidence: 99%